Pengembangan Adaptive E-Learning Sistem Berbasis Vark Learning Style Pada Materi IP Address - Nindia Rada Kusworo; Yerry Soepriyanto; Arafah Husna (Universitas Negeri Malang, 2021)
Abstract: The learning system in SMK targets 25% material and 75% practice. The students' time while in school will spend with practices and less time exploring materials. An alternative is needed so that students can optimize their understanding of the materials without cutting practicals time at school. Adaptive E-Learning System (AES) implements learning which refers to differences in student characteristics in the form of learning styles. Learning styles are the ways and conditions in which students efficiently and effectively understand, process, store, and recall what they have learned. Development models applied in this study is the multimedia instructional design model by Lee & Owens. To see the feasibility of the AES program, a feasibility test from media experts and material experts is required using a questionnaire with a scale of 1-5. The results of review from media experts and material experts show positive values with the majority of value being 5 and 4 so that the application program is categorized as suitable for use. The result of this development is an AES program that can identify student learning styles and provide material according to their learning styles. Abstrak: Sistem pembelajaran di SMK menargetkan 25% materi dan 75% praktik. Waktu siswa selama di sekolah akan habis dengan praktik dan sedikit waktu dalam mendalami materi. Diperlukan alternatif sehingga siswa dapat mengoptimalkan pemahaman materi tanpa perlu memotong waktu praktik di sekolah. Adaptive E-Learning System (AES) menerapkan pembelajaran yang mengacu pada perbedaan karakteristik siswa berupa gaya belajar. Gaya belajar merupakan cara dan kondisi dimana siswa secara efisien dan efektif memahami, mengolah, menyimpan dan mengingat kembali apa yang mereka pelajari. Model pengembangan yang diterapkan dalam penelitian ini adalah model multimedia instructional design oleh Lee & Owens. Untuk mengetahui kelayakan program AES maka diperlukan uji kelayakan dari ahli media dan ahli materi dengan menggunakan angket dengan skala 1-5. Hasil review dari ahli media dan ahli materi menunjukkan nilai positif dengan mayoritas nilai adalah 5 dan 4 sehingga program aplikasi dikategorikan layak digunakan. Hasil pengembangan ini merupakan program Adaptive e-learning system yang dapat mengidentifikasi gaya belajar siswa dan memberikan materi sesuai dengan gaya belajarnya.